PENGARUH PENGAWASAN LANGSUNG TERHADAP KINERJA PEGAWAI DI LINGKUNGAN INSPEKTORAT KOTA PADANGSIDIMPUAN SUMATERA UTARA - Ismail Marzuki Siregar; Marlon Sihombing (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2021)
This research is performed using census research method. In this research , the population is all employees of 32 people in the Regional Inspectorate of Padangsidimpuan. The data analysis technique used is descriptive and quantitative analysis. The results show that employees in the Office of the Regional Inspectorate of Padangsidimpuan have direct monitoring by a category quite good. It can also be seen from the quality, quantity, use of worktime and employee cooperationFrom the research that has been conducted at the Regional Inspectorate of Padangsidimpuan, there is a positive relationship between direct monitoring with the employee 's performance. The results of single regression analysis also shows a positive influence of the variable direct monitoring to the employee performance . If an increase in direct monitoring, the employee 's performance will increase as well. It can be concluded that the direct monitoring contributes to employee performance variables in the Regional Inspectorate Padangsidimpuan of 99.36 %